Methods of Psychological Self-Regulation as a Means of Preventing Unfavorable Conditions in Professional Activities - Morozova, M.I.; Kupchik, K.V.; Yashneva, M.Yu (Extreme Psychology and Personal Safety, 2024)
The purpose of the study was to analyze existing methods of self-regulation for the prevention of negative conditions and, on its basis, to select the most effective method of self-regulation and test it for representatives of high-risk professions. The research conducted in 2024, involved 28 reserve officers (average age 25 (+2,5) years; 100% men). The subjects were equally divided into 2 groups: experimental and control randomly. Methods: assessment of the state of reduced performance (DORS, the scale of neuropsychic tension (T.N. Nemchin), the questionnaire of the degree of chronic fatigue (A.B. Leonova). Method of experimental influence: progressive muscle relaxation (in our modification). Two sessions were conducted, lasting 20 minutes, according to the following scheme: scanning, tension, and then relaxation of certain muscle groups and repeated scanning. Statistical methods: comparative analysis by the Mann-Whitney criterion, differential analysis ANOVA (Fisher criterion) (independent variable: muscle relaxation training - we identified 2 levels in it. 1 - without training, 2 - with training; dependent variable - unfavorable mental states), arithmetic mean of all indicators, standard deviation of indicators, comparative analysis by the Wilcoxon criterion. All calculations were performed using the STATISTICA program. Results: the most pronounced unfavorable states in reserve officers were: neuropsychic tension, monotony, satiety and stress. After the training, there was a reliable decrease in the level of monotony and the degree of chronic fatigue. Conclusion: the method of progressive muscle relaxation (in our modification) has a positive effect on such unfavorable conditions as satiety and the degree of chronic fatigue and can be used as a preventive measure for these negative conditions in reserve officers undergoing training in a military registration specialty. Деятельность специалистов служебной сферы связана с различными стрессами и риском, что напрямую влияет на их психологическое состояние. В связи с этим актуальна разработка методов психологической саморегуляции для профилактики неблагоприятных изменений. Испытуемые офицеры запаса - 28 человек, мужчины, средний возраст 25 (+2,5) лет. Испытуемые были поровну разделены на 2 группы, экспериментальную и контрольную, случайном образом. Методы: оценка состояния сниженной работоспособности (ДОРС), шкала нервно-психического напряжения НПН (Т.Н. Немчин), опросник «Степень хронического утомления» (А.Б. Леонова). Метод экспериментального воздействия: прогрессивная мышечная релаксация (в нашей модификации). Проводилось два занятия продолжительностью 20 минут по следующей схеме: сканирование, напряжение, а далее расслабление определенных групп мышц и повторное сканирование. Методы статистики: сравнительный анализ по критерию Манна-Уитни, дифференциальный анализ ANOVA (критерий Фишера) (независимая переменная: обучение мышечной релаксации - мы выделили в ней два уровня: первый - без обучения, второй - с обучением; зависимая переменная - неблагоприятные психические состояния), среднее арифметическое всех показателей, стандартное отклонение показателей, сравнительный анализ по критерию Вилкоксона. Все расчеты проводились при помощи программы STATISTICA. Результаты: наиболее выраженные неблагоприятные состояния у офицеров запаса - нервно-психическое напряжение, монотония, пресыщение и стресс. После проведенного тренинга произошло достоверное снижение уровня монотонии и степени хронического утомления. Вывод: метод прогрессивной мышечной релаксации (в нашей модификации) оказывает положительное влияние на такие неблагоприятные состояния, как пресыщение и степень хронического утомления, и может использоваться в качестве профилактики данных негативных состояний у офицеров запаса, проходящих обучение по военно-учетной специальности.